Farocki/Godard. Film as Theory - Pantenburg, Volker (Film Culture in Transition, 2015)
There is a tension between the requirements of theoretical abstraction and the capacities of the film medium, where everything that we see on screen is concrete: A train arriving at a station, a tree, bodies, faces. Since the complex theories of montage in Soviet cinema, however, there have continuously been attempts to express theoretical issues by combining shots, thus creating a visual form of thinking. This book brings together two major filmmakers-French New Wave master Jean-Luc Godard and German avant-gardist Harun Farocki to explore the fundamental tension between theoretical abstraction and the capacities of film itself, a medium where everything seen onscreen is necessarily concrete. Volker Pantenburg shows how these two filmmakers explored the potential of combined shots and montage to create "film as theory."